The Problem of Social Order in the Contemporary Rational Choice Approach and in Max Weber’s Interpretive Sociology - Norkus, Zenonas (Sociologija. Mintis ir veiksmas, 2005)
The idea that the utilitarian explanation of social order is dead, established in Talcott Parsons’ major work „The Structure of Social Action“, had been predominating among sociologists for a long time. Indeed, Parsons was commonly thought to be the one who buried the utilitarian explanation. The situation changed after the rise of Rational Choice Approach which could be called a neo-utilitarian social theory. It reanimated utilitarian explanation of social order, recycling it in the framework of the game theory. This article (1) profiles methodological singularity of the neo-utilitarian explanation by describing it as „protosociological“ as opposed to sociological (empirical) application of the rational choice theory; (2) discloses and criticizes the implicit assumption of Parson’s „convergence thesis“ that the problem of social order was conceived in the same way in all significant contributions of the classical sociological tradition; (3) compares Weberian ideas on social order with those in the neoutilitarian works and discusses the significance of Max Weber’s theoretical legacy for the current work on the problem of social order.